2015
DOI: 10.1111/ajgw.12190
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing domestication of wine yeast: past, present and future

Abstract: Yeast starter cultures for winemaking have traditionally been developed from successful fermentation isolates. Over the past 10-20 years there has been a move to harness genetic techniques to improve production strains. The approaches to achieve this have been similar to those applied in the agricultural sector for crop and livestock development. Thus, domestication of wine yeasts now involves hybridisation, mutagenesis, selection and screening. There is also a growing interest in tapping into isolates of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 115 publications
2
9
0
Order By: Relevance
“…Based on sensory and chemical data correlation analysis, D‐galacturonic acid, which is related to the pectin addition and non‐ Saccharomyces utilization of pectin, had a significant positive correlation with the buttery aroma ( p = 0.05; r = 0.76). Previous research has indicated that pectinase and NSY can increase the flavor and aroma intensities, which may explain the positive correlation with the buttery flavor (Chambers et al., 2015; Sieiro et al., 2012). However, limited previous research has been done on the influence higher pH have on wines produced with NSY.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on sensory and chemical data correlation analysis, D‐galacturonic acid, which is related to the pectin addition and non‐ Saccharomyces utilization of pectin, had a significant positive correlation with the buttery aroma ( p = 0.05; r = 0.76). Previous research has indicated that pectinase and NSY can increase the flavor and aroma intensities, which may explain the positive correlation with the buttery flavor (Chambers et al., 2015; Sieiro et al., 2012). However, limited previous research has been done on the influence higher pH have on wines produced with NSY.…”
Section: Resultsmentioning
confidence: 94%
“…Recent studies have focused on the reduction in ethanol concentrations (reductions of 0.9–2.2%) by using sequential or coinoculation of NSY and S. cerevisiae (Aplin et al., 2019; Canonico et al., 2019; Contreras et al., 2015). Additionally, NSY have also been shown to influence pH, titratable acidity (TA), and volatile acidity due to the increase in acetic acid, succinic acid, and lactic acid production (Chambers et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A critical aspect for studying yeast interactions during fermentation is to evaluate the yeast population, especially living cells. The traditional method used for determining the yeast living cells during alcoholic fermentation is based on colony counting in different culture media, which takes 2 or 3 days and might cause some deviations [ 27 , 70 ]. In mixed or spontaneous fermentations, to differentiate and count the different yeast species, we need to use selective or differential media [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In winemaking, the use of pure yeast cultures allows a better control of the fermentations; however, it can also reduce the production of some desired metabolites, both from the yeast's metabolism itself and from transformation of precursors present in the grape must. For this purpose, it is increasingly seen more convenient to use different yeast genera and species, which can contribute or influence the chemical composition and the flavor of wines [4,5,12,13,17,19,21]. The volatile compounds produced by the strains analyzed in this study are of great aromatic value, especially the production of ethyl hexanoate and ethyl octanoate (apple note), isoamyl acetate (banana note), and phenyl ethyl acetate (fruity, floral notes), compounds which could render (in the appropriate amounts) good organoleptic characteristics to a wine.…”
Section: Discussionmentioning
confidence: 99%